Pathways for the Intercultural Hermeneutics of Chinese Excellent Traditional Culture - Jiang, Meng; Audreyjanice Manoppo (Journal of Educational Theory and Practice, 2026)
Against the backdrop of strengthening international communication capacity and building a culturally strong nation in the new era, the international communication of fine traditional Chinese culture has increasingly become an important task for enhancing China’s cultural soft power and expanding the influence of Chinese culture. At present, although the international communication of fine traditional Chinese culture has formed a basic pattern characterized by the participation of multiple actors and the parallel use of multiple channels, it still faces such problems as insufficient depth in content interpretation, difficulties in discourse transformation, inadequate platform adaptation, weak coordination among actors, and an incomplete evaluation system for communication effectiveness, all of which constrain the improvement of overall communication performance. On the basis of sorting out the practical foundations and major problems of the international communication of fine traditional Chinese culture, this paper, centering on its goals and overall framework, proposes a structure guided by the enhancement of national international communication capacity, supported by a value-interpretation system for Chinese civilization and an international communication platform system, and focused on value interpretation, audience segmentation, and digital innovation. It further discusses the issue from two dimensions: mechanism construction with coordinated improvement, and pathway design with practical advancement. The study argues that improving the effectiveness of the international communication of fine traditional Chinese culture requires adherence to the unity of cultural subjectivity and internationalized expression, the coordinated advancement of content supply, discourse transformation, platform support, and feedback evaluation, as well as the integrated planning of communication layout, audience-specific communication, digital empowerment, and practical guarantees, thereby promoting a deeper transformation from merely “being communicated abroad” to “achieving effective communication.”